A new indocyanine green fluorescence lymphography protocol for diagnostic assessment of lower limb lymphoedema. Issue 11 (November 2022) - Suami, Hiroo; Thompson, Belinda; Mackie, Helen; Blackwell, Robbie; Heydon-White, Asha; Blake, Fiona Tisdall; Boyages, John; Koelmeyer, Louise
Summary: Introduction: The lower limbs are a common body site affected by chronic edema. Imaging examination of the lymphatic system is useful to diagnose lymphoedema, identify structural changes in individuals, and guide interventional strategies. In this study, we used a protocol combining indocyanine green (ICG) lymphography and ICG-guided manual lymphatic drainage (MLD) for the diagnostic assessment of lower limb lymphoedema. Materials and methods: Patients with lower limb lymphoedema were divided into three groups by their medical history: primary, secondary cancer-related, or secondary non-cancer-related. ICG lymphography was conducted in three phases: initial observation, MLD to accelerate ICG dye transit and reduce imaging time, and imaging data collection. Lymphatic drainage regions were recorded, and the MD Anderson Cancer Center ICG staging was applied. We collected routine lymphoedema assessment data, including limb volume and bioimpedance spectroscopy measurements. Results: Three hundred and twenty-six lower limbs that underwent ICG lymphography were analyzed. Eight drainage regions were identified. The ipsilateral inguinal and popliteal were recognized as the original regions, and the remaining six regions were considered compensatory regions that occur only in lymphoedema. More than half of the secondary cancer-related lower limb lymphoedema (57.6%) continued to drain to the ipsilateral inguinal region. The incidence of drainage to the ipsilateral inguinal region was even higher for the primary (82.8%) and secondary non-cancer-related (87.1%) groups. Significant associations were observed between cancer-related lymphoedema and the presence of compensatory drainage regions. Conclusions: We proposed a prospective ICG lymphography protocol for the diagnostic assessment of lower limb lymphoedema in combination with MLD. Eight drainage regions were identified, including two original and six compensatory regions.